REFORMASI SISTEM PENYELESAIAN SENGKETA AGRARIA DENGAN MEMBENTUK PERADILAN PERTANAHAN - DT Nouvendi SK, DT Nouvendi SK; Sumanto, Listyowati (Ensiklopedia of Journal, 2025)
Agrarian disputes in Indonesia are a classic, recurring problem due to overlapping regulations, weak legal certainty, and the lack of integration of authorized dispute resolution institutions. This situation creates uncertainty for the public and investors, and hampers national economic development. This study aims to analyze the weaknesses of the current agrarian dispute resolution system and propose the establishment of a Land Court as an effort to reform agrarian law that is more effective, efficient, and equitable. The research method used is normative juridical research, with descriptive nature. Secondary data is analyzed qualitatively. Conclusions are drawn using deductive logic. The results indicate that the resolution of agrarian disputes through general and state administrative courts has not been able to provide certainty and substantive justice for the parties, due to the limited competence of judges and the complexity of agrarian law. Therefore, the establishment of a Land Court is a strategic step in realizing the reform of the national agrarian legal system oriented towards social justice, legal certainty, and public welfare, as mandated by Article 33 of the 1945 Constitution. Keywords: Legal Reform, Agrarian Disputes, Special Courts, Legal Certainty, Social Justice